Pengaruh Karakteristik Personal, Komunikasi serta Karakteristik Struktur Organisasi terhadap Komitmen Organisasi (Studi Pada Pengurus Unit Aktivitas Mahasiswa (UAM) FEB UNISMA 2020-2021) - Abdullah Aslim; Eka Farida; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of personal characteristics, communication and organizational structure characteristics on organizational commitment. The research used is descriptive quantitative method. The population in this study were 463 UAM FEB UNISMA administrators for the 2020-2021 period. While the sample used is probability sampling with 82 samples. The results of this study indicate that simultaneously personal characteristics, communication, and organizational characteristics have a significant effect on organizational commitment, while partially organizational structure characteristics have no significant effect on organizational commitment. Keywords: Personal Characteristics, Communication, Organizational Structure Characteristics, Organizational Commitment